2010
DOI: 10.1016/j.orl.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

On interval-subgradient and no-good cuts

Abstract: Interval-gradient cuts are (nonlinear) valid inequalities for nonconvex NLPs defined for constraints g(x) ≤ 0 with g being continuously differentiable in a box [x,x]. In this paper we define intervalsubgradient cuts, a generalization to the case of nondifferentiable g, and show that no-good cuts (which have the form x−x ≥ ε for some norm and positive constant ε) are a special case of interval-subgradient cuts whenever the 1-norm is used. We then briefly discuss what happens if other norms are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
(21 reference statements)
0
21
0
Order By: Relevance
“…In the case where an integer solution found by CPLEX at the root node appears in the tabu list, CPLEX stops and no new integer feasible solution is provided to FP 4 . In such a case, we amend problem (9) with a no-good cut [17] which excludes the solution and we call CPLEX again. Avoid cycling when solving (9) by rounding.…”
Section: Fp Variants and Preliminary Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case where an integer solution found by CPLEX at the root node appears in the tabu list, CPLEX stops and no new integer feasible solution is provided to FP 4 . In such a case, we amend problem (9) with a no-good cut [17] which excludes the solution and we call CPLEX again. Avoid cycling when solving (9) by rounding.…”
Section: Fp Variants and Preliminary Resultsmentioning
confidence: 99%
“…Note that while (18) could seem to require that each g for ∈ C be a differentiable function, this is only assumed for the sake of notational simplicity: notoriously, subgradients of nondifferentiable convex functions can be used as well (e.g. [17]). …”
Section: Addressing the Convex Minlp (9)mentioning
confidence: 99%
See 2 more Smart Citations
“…Cutting planes developed for MINLP include those based on: pseudo-convex MINLP problems , outer approximation of convex terms and linearization of other convex underestimators (Tawarmalani and Sahinidis, 2005;, multi-term quadratic expressions (Bao et al, 2009;Luedtke et al, 2012;, multilinear functions (Rikun, 1997;Belotti et al, 2010b;Qualizza et al, 2012), optimizing convex quadratic functions over nonconvex sets (Bienstock and Michalka, 2014), and other cutting plane classes based on nonlinear functional forms (D'Ambrosio et al, 2010;Richard and Tawarmalani, 2010). A review on cutting plane methods for MINLP can be found in Nowak (2005); multivariable and multiterm relaxations are typically favoured for MINLP because the tightest convex relaxation of each individual is not typically equivalent to the tightest possible relaxation of the entire MINLP (Westerlund et al, 2011).…”
Section: Cutting Planesmentioning
confidence: 99%